2012
DOI: 10.1029/2012ja017974
|View full text |Cite
|
Sign up to set email alerts
|

Hot and cold ion outflow: Spatial distribution of ion heating

Abstract: [1] Ions apparently emanating from the same source, the ionospheric polar cap, can either end up as energized to keV energies in the high-altitude cusp/mantle, or appear as cold ions in the magnetotail lobes. We use Cluster observations of ions and wave electric fields to study the spatial variation of ion heating in the cusp/mantle and polar cap. The average flow direction in a simplified cylindrical coordinate system is used to show approximate average ion flight trajectories, and discuss the temperatures, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 56 publications
(88 reference statements)
5
83
1
Order By: Relevance
“…However, during storm time, accelerated O + was observed in the cusp. Nilsson et al (2012) showed consistent results with a little acceleration in the polar cap and lobes but significant heating and subsequent acceleration in the cusp and plasma mantle. They did however not divide their data according to geomagnetic activity.…”
Section: Introductionsupporting
confidence: 67%
“…However, during storm time, accelerated O + was observed in the cusp. Nilsson et al (2012) showed consistent results with a little acceleration in the polar cap and lobes but significant heating and subsequent acceleration in the cusp and plasma mantle. They did however not divide their data according to geomagnetic activity.…”
Section: Introductionsupporting
confidence: 67%
“…There are three main regions of outflow at high latitudes: the auroral oval, the cusp, and the polar cap. The auroral oval and the cusp are regions of intense ion outflow in response to strong energy inputs like Poynting flux, particle precipitation, and the work done by strong field-aligned electric fields accelerating ions upwards (Lockwood et al, 1985;Zheng et al, 2005;Moore and Khazanov, 2010;Nilsson et al, 2012). In the absence of such energy inputs, the main source of energy for ion outflow in the polar cap is solar illumination.…”
Section: Introductionmentioning
confidence: 99%
“…But the ions with the lowest energies may be convected across the polar cap and mix with the polar wind ions (e.g. Green and Waite Jr., 1985;Nilsson et al, 2012), so that it is not always possible to discern polar wind ions from the ions originating in the cusp. This also provides another possible explanation for the O + observed above the polar caps and in the lobes.…”
Section: Introductionmentioning
confidence: 99%
“…If only the field-aligned portion is included, the temperature will be reduced to < 100 eV. Note also that because of mirror force, the temperature perpendicular to the magnetic field may indicate some heating (see also Nilsson et al, 2012, for Cluster studies of ion heating throughout the polar cap magnetosphere).…”
Section: Observationsmentioning
confidence: 99%